2022
DOI: 10.1002/aenm.202201520
|View full text |Cite
|
Sign up to set email alerts
|

Optically and Mechanically Engineered Anti‐Reflective Film for Highly Efficient Rigid and Flexible Perovskite Solar Cells

Abstract: phase stabilizing, [8] charge carrier management, [9] pseudo-halide anion engineering, [10] and intact 2D/3D perovskite bilayer employment; [5] up to 25.5% certificated PCE of the device has been reported.Most of the previous investigations were focused on inner device factors such as materials and junctions of the PSC. [11][12][13][14][15][16][17] However, gathering entire light wavelength (350-850 nm) and putting it into the PSC are equally important to enhancing the PCE by controlling the mechanism inside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
(74 reference statements)
0
20
0
Order By: Relevance
“…Once the ARC was used in the devices, the main increase of the photovoltaic parameters is the J SC , and the V OC and FF remain unchanged. 196,197 For example, Choi fabricated a sticker-type ultra-thin (20 μm) perfluoropolyether AR film (SUPA) with a refractive index of 1.34 and light transition efficiency of 98.3% (Fig. 15a), and the J SC of the SUPA-used PerSCs reached 26.63 mA cm −2 , which increased by 3.82% compared with the control device.…”
Section: Strategies For High Efficiency 2d Perscsmentioning
confidence: 99%
“…Once the ARC was used in the devices, the main increase of the photovoltaic parameters is the J SC , and the V OC and FF remain unchanged. 196,197 For example, Choi fabricated a sticker-type ultra-thin (20 μm) perfluoropolyether AR film (SUPA) with a refractive index of 1.34 and light transition efficiency of 98.3% (Fig. 15a), and the J SC of the SUPA-used PerSCs reached 26.63 mA cm −2 , which increased by 3.82% compared with the control device.…”
Section: Strategies For High Efficiency 2d Perscsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Previous studies have demonstrated the importance of suppressing reflections at the interface to achieve high transparency. [1,[10][11][12] At the surface, which is the interface between different materials, light is reflected owing to the different refractive index (n) of each material. Many researchers have developed optical films/membranes to which surface multilayer coatings or nanostructures can be applied to reduce light reflection.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have developed optical films/membranes to which surface multilayer coatings or nanostructures can be applied to reduce light reflection. [3,[10][11][12][13][14][15][16] This prevents reflection along the path of light by gradually reducing the refractive index value at the interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] In recent years, scientists have developed a strong interest in the study of flexible single-junction perovskite SCs. [26][27][28][29][30] In just 9 years, the efficiency of flexible perovskite SCs has increased dramatically (from 2.6% to 23.6%). [7,31] However, this efficiency is still far from the certified efficiency of 25.7% compared with single-junction rigid PSCs.…”
mentioning
confidence: 99%